Mein Kampf - Hitler, Adolf, 1889-1945. (New Delhi : Elite Minds Inc., 2009)
Tells the story of Hitler's life and his social and political philosophy.
"The official Nazi English translation."
"This edition was first published between 1937-44 by Eher Nachf, G.M.B.H (Nazi Printing Office, Germany). This edition has been reformatted and compiled and is copyrighted by Elite Minds Inc."--Publisher's note.
Keywords: Hitler, Adolf, -- 1889-1945 -- Psychology; Hitler, Adolf, -- 1889-1945.; Nationalsozialistische Deutsche Arbeiter-Partei.; Germany -- Politics and government -- 20th century